Synthetic Na/K-birnessite for efficient management of Sr(II) from nuclear waste. Issue 6 (December 2018) - Bevara, Samatha; Giri, Prema; Achary, S. Nagabhusan; Bhallerao, G.; Mishra, Raman K.; Kumar, Amar; Kaushik, Chetan P.; Tyagi, Avesh Kumar
Graphical abstract: Highlights: Two birnessite type Na and K phyllomanganates were prepared by oxidation of Mn(OH)2 in presence of NaOH/KOH. Sr 2+ uptake behaviors of Na/K-Birnessite have been studied using radioactive and stable Sr 2+ ions. Kd of the order 10 4 over a wide range of pH (2 to 14) for Sr 2+ uptake is reported for both Na/K-Birnessites. A promising and cost effective mode for management of 90 Sr 2+ is established by the phyllomanganates. Correlation between crystal structure and ion exchange properties will be useful to design new ion exchangers. Abstract: The efficient separation for alternate use and management of 90 Sr in nuclear waste is an important research activity in nuclear power industries. Herein we have demonstrated an efficient separation of Sr 2+ by birnessite type sodium and potassium phyllomanganates (Ax Mn2 O4 -yH2 O; A = Na + and K + ). Both the materials were prepared by oxidation of Mn(OH)2 by flowing oxygen atmosphere in presence of large excess of alkali hydroxide. Mn(OH)2 was prepared by precipitation method using solutions of MnCl2 and NaOH or KOH. The XRD studies revealed that both materials have layered monoclinic (C2/m) structures made of sheets of edge shared MnO6 octahedra. The Na + or K + ions were located in between these layers and provide charge neutrality to the structure. From thermogravimetric and XRD studies, the compositions of the prepared phyllomanganates are found to be Na0.5 Mn2 O4 -0.96H2 O (NMO) and K0.5 Mn2 O4 -0.6H2 O (KMO). The ion exchange studies carried out using radioactive 85 Sr 2+ solutions revealed large distribution constant (Kd ) in a wider range of pH (2 to 14). Maximum Kd (27, 000 mL/g) for NMO is observed in neutral medium which decreased to ∼19, 000 mL/g at pH 14, while the Kd (∼22, 000 mL/g) of KMO is relatively insensitive to pH. Higher preference of Sr 2+ ions over Na + and K + have been concluded from the kinetics of exchange process. Ion exchange capacities of NMO and KMO are: 9.64 mmol/g and 1.09 mmol/g, respectively. Interference studies with several commonly present ions in nuclear waste like Al 3+, Ca 2+, H + and Na + ions, indicated appreciable interference only from Al 3+ .